Land Rights Registration for the Placement of Linear Objects: Comparative Legal Analysis (EUROPEAN AND ASIAN LAW REVIEW, 2025)
The article examines the existing legal mechanisms for land rights in case of placement of linear objects abroad. The author analyzes the legal regulation of Germany, France, Austria, Great Britain, Moldova and other states, as well as doctrinal sources devoted to the study of land use regulations in the placement and operation of linear objects. The author concludes that the legal mechanisms for establishing land rights for the installation of engineering networks are based on public law tools, which are conditioned by the need to create conditions for carrying out activities of public interest.
Keywords: linear object; engineering and technical support networks; easement; public easement; public interests